2018
DOI: 10.2196/mental.9146
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ Perspectives on the Facilitators and Barriers to Engaging With Digital Mental Health Interventions in the Workplace: Qualitative Study

Abstract: BackgroundPrevalence rates of work-related stress, depression, and anxiety are high, resulting in reduced productivity and increased absenteeism. There is evidence that these conditions can be successfully treated in the workplace, but take-up of psychological treatments among workers is low. Digital mental health interventions delivered in the workplace may be one way to address this imbalance, but although there is evidence that digital mental health is effective at treating stress, depression, and anxiety i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 67 publications
6
78
0
Order By: Relevance
“…However, if a DSMS is used at work, the process is visible to colleagues or supervisors and therefore no longer anonymous. Supplementary, the requirement for high mobility can also have disadvantages at the workplace, as there may be difficulties in prioritizing time and separating work and therapy [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, if a DSMS is used at work, the process is visible to colleagues or supervisors and therefore no longer anonymous. Supplementary, the requirement for high mobility can also have disadvantages at the workplace, as there may be difficulties in prioritizing time and separating work and therapy [4].…”
Section: Discussionmentioning
confidence: 99%
“…Having a direct link to the program to make it faster and easier for participants was endorsed by this study. Although studies have found results consistent with this finding [ 51 ], more research is needed to find the optimal medium for reminders to motivate program use.…”
Section: Discussionmentioning
confidence: 58%
“…Several participants advocated for Welbot to allow individualised preferences in relation to the frequency and timing of nudges and the option to sync these to online calendars. Personalised tailoring of information within digital health interventions has been reported by users in previous research as an important facilitator of continued engagement [42][43][44]. Indeed, more recent versions of Welbot than what was used in the current study offer this function.…”
Section: Discussionmentioning
confidence: 64%
“…In relation to the negative attributes of the digital intervention, feeling self-conscious whilst carrying out the activities at their desk was reported in previous studies that specifically used health interventions in the workplace. Indeed, research has found that not having a private space within the workplace to access a digital mental health intervention and feeling exposed using the intervention whilst sat at their desk were barriers to engagement [43]. Whilst participants reported on the positive and negative attributes of Welbot, they did offer useful suggestions for improvements to the digital health intervention.…”
Section: Discussionmentioning
confidence: 99%